The role of tonic glycinergic conductance in cerebellar granule cell signalling and the effect of gain‐of‐function mutation. (2nd April 2019) - McLaughlin, Catherine; Clements, John; Oprişoreanu, Ana‐Maria; Sylantyev, Sergiy
Abstract : Key points: A T258F mutation of the glycine receptor increases the receptor affinity to endogenous agonists, modifies single‐channel conductance and shapes response decay kinetics. Glycine receptors of cerebellar granule cells play their functional role not continuously, but when the granule cell layer starts receiving a high amount of excitatory inputs. Despite their relative scarcity, tonically active glycine receptors of cerebellar granule cells make a significant impact on action potential generation and inter‐neuronal crosstalk, and modulate synaptic plasticity in neural networks; extracellular glycine increases probability of postsynaptic response occurrence acting at NMDA receptors and decreases this probability acting at glycine receptors. Tonic conductance through glycine receptors of cerebellar granule cells is a yet undiscovered element of the biphasic mechanism that regulates processing of sensory inputs in the cerebellum. A T258F point mutation disrupts this biphasic mechanism, thus illustrating the possible role of the gain‐of‐function mutations of the glycine receptor in development of neural pathologies. Abstract: Functional glycine receptors (GlyRs) have been repeatedly detected in cerebellar granule cells (CGCs), where they deliver exclusively tonic inhibitory signals. The functional role of this signalling, however, remains unclear. Apart from that, there is accumulating evidence of the important role of GlyRs in cerebellar structures in development of neural pathologies such as hyperekplexia, which can be triggered by GlyR gain‐of‐function mutations. In this research we initially tested functional properties of GlyRs, carrying the yet understudied T258F gain‐of‐function mutation, and found that this mutation makes significant modifications in GlyR response to endogenous agonists. Next, we clarified the role of tonic GlyR conductance in neuronal signalling generated by single CGCs and by neural networks in cell cultures and in living cerebellar tissue of C57Bl‐6J mice. We found that GlyRs of CGCs deliver a significant amount of tonic inhibition not continuously, but when the cerebellar granule layer starts receiving substantial excitatory input. Under these conditions tonically active GlyRs become a part of neural signalling machinery allowing generation of action potential (AP) bursts of limited length in response to sensory‐evoked signals. GlyRs of CGCs support a biphasic modulatory mechanism which enhances AP firing when excitatory input intensity is low, but suppresses it when excitatory input rises to a certain critical level. This enables one of the key functions of the CGC layer: formation of sensory representations and their translation into motor output. Finally, we have demonstrated that the T258F mutation in CGC GlyRs modifies single‐cell and neural network signalling, and breaks a biphasic modulation of the AP‐generating machinery. Key points: A T258F mutation of the glycine receptor increases the receptor affinity to endogenous agonists, modifies single‐channel conductance and shapes response decay kinetics. Glycine receptors of cerebellar granule cells play their functional role not continuously, but when the granule cell layer starts receiving a high amount of excitatory inputs. Despite their relative scarcity, tonically active glycine receptors of cerebellar granule cells make a significant impact on action potential generation and inter‐neuronal crosstalk, and modulate synaptic plasticity in neural networks; extracellular glycine increases probability of postsynaptic response occurrence acting at NMDA receptors and decreases this probability acting at glycine receptors. Tonic conductance through glycine receptors of cerebellar granule cells is a yet undiscovered element of the biphasic mechanism that regulates processing of sensory inputs in the cerebellum. A T258F point mutation disrupts this biphasic mechanism, thus illustrating the possible role of the gain‐of‐function mutations of the glycine receptor in development of neural pathologies.